Eulasia (Rudeulasia) daccordii, a new species from southern Levant, with notes on E. pietschmanni Breit and E. baumanni Mitter (Coleoptera: Scarabaeoidea: Glaphyridae) - Uliana, Marco; Sabatinelli, Guido (Zootaxa, 2013)
Eulasia daccordii new species is described from Jordan, West Bank, and Israel, where it is known from the Jordan Valley and the Negev. It was previously confused with E. pietschmanni Breit, to which it is very similar and from which it can be recognized mainly for the structure and distribution of the pronotal setae and the shape of the protibia of males. Remarks on distribution and colour range of E. pietschmanni Breit are provided, and its year of description is corrected from 1919 to 1920. In addition, taxonomic and diagnostic remarks on the poorly known sympatric species E. baumanni Mitter are presented: it is clarified that this poorly known taxon is related to E. papaveris (Sturm), whose Levantine populations require a taxonomic reassessment.